A climate resilience research renewal agenda: learning lessons from the COVID-19 pandemic for urban climate resilience. (9th August 2022) - Pelling, Mark; Chow, Winston T. L.; Chu, Eric; Dawson, Richard; Dodman, David; Fraser, Arabella; Hayward, Bronwyn; Khirfan, Luna; McPhearson, Timon; Prakash, Anjal; Ziervogel, Gina
ABSTRACT: Learning lessons from the COVID-19 pandemic opens an opportunity for enhanced research and action on inclusive urban resilience to climate change. Lessons and their implications are used to describe a climate resilience research renewal agenda. Three key lessons are identified. The first lesson is generic, that climate change risk coexists and interacts with other risks through overlapping social processes, conditions and decision-making contexts. Two further lessons are urban specific: that networks of connectivity bring risk as well as resilience and that overcrowding is a key indicator of the multiple determinants of vulnerability to both COVID-19 and climate change impacts. From these lessons three research priorities arise: dynamic and compounding vulnerability, systemic risk and risk root cause analysis. These connected agendas identify affordable and healthy housing, social cohesion, minority and local leadership and multiscale governance as entry points for targeted research that can break cycles of multiple risk creation and so build back better for climate change as well as COVID-19 in recovery and renewal.